The effect of dispersing agent on the formation of aluminium nitride nanoparticles/whiskers. (15th April 2016) - Pan, D.; Wang, K.; Ding, J.; Liu, Y.; Zhang, P.
Abstract : The effect of the amount of dispersing agent on the formation of aluminium nitride (AlN) nanoparticles/whiskers is presented. Various levels of the dispersant [rice bran (RB)] concentration, mass ratio of Al/RB ranging from 0.43 (30:70) to 2.33 (70:30), were systematically investigated. After the heat treatment in a nitrogen atmosphere, all samples with different RB contents could be transformed to AlN nanoparticles and nanowhiskers with trace graphite. In this experiment, the dispersant concentration in the starting mixture not only affects the morphologies of the resultant AlN (particles/whiskers) but also makes the morphology of the AlN whiskers evolve. The mechanisms for the formation and the evolution of AlN whiskers are discussed.